Fostering Resilience in Costa Rican Teachers: An Analysis from a Restorative Practices Perspective - de Mézerville López, Claire Marie (2019)
This opinion paper explores the importance of fostering resiliency in Costa Rican high school teachers. Resilience in educational settings is analysed from the perspective of restorative practices, understood as proactive actions to strengthen the school community through repairing harm and restoring human relationships. Restorative practices based on principles like high control and high support, restorative questioning and positive affect will be described. Teachers’ resilience will be explored through the models of compassionate witnessing.1 and the relational care ladder.2 Teachers that are capable of fostering resilience development with their students in their own classrooms will become resilient themselves. Community based approaches are acknowledged as well as the necessary involvement of school systems and policy makers. Costa Rica’s results from the latest report on the State of Education3 will identify particular issues where teachers’ resilience is relevant in order to prevent burnout, promote student permanence and increase life skills such as self care and appropriate attention to high need - high risk students.